Dumbbell shape EBG structure — Worth to EBG assisted microwave filter designing - S. M. Shakil Hassan; Mohammad Nurunnabi, Mollah; Mohd Abdur, Rashid; Nur Hafeizza, Ramly; Mardianaliza, Othman (Institute of Electrical and Electronic Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/